Boi-bumbá :tradição da comemoração da identidade cultural nordestina em Porto Velho-RO - Santos, Josimar Batista dos (2015)
The research analyzed the role of tradition in the celebration of the boi-bumbá the consolidation of northeastern cultural identity in Porto Velho. For this, we studied the establishment of tradition in commemoration of northeastern cultural identity in the merriment of the boi-bumbá. The work focused on the study of the construction of cultural identity of northeastern migrants in Porto Velho and, as the tradition of celebrating, boi-bumbá influenced for this cultural event became symbol of that social roup. This process of boi-bumbá celebration of tradition comes over time getting many influences, as there are cultural appropriations, that is, a cultural hybridity, a consequence of the mass communication of late post-modern society. Therefore, the research contributed to emphasize relationships of the Northeastern migratory movement has today in Porto Velho, in the local culture, in folklore, in short, the cultural identity of porto-velhense society.